Systemic multicompartmental effects of the gut microbiome on mouse metabolic phenotypes - Sandrine P Claus; Tsz M Tsang; Yulan Wang; Olivier Cloarec; Eleni Skordi; François‐Pierre Martin; Serge Rezzi; Alastair Ross; Sunil Kochhar; Elaine Holmes; Jeremy K Nicholson (Molecular Systems Biology)
Abstract To characterize the impact of gut microbiota on host metabolism, we investigated the multicompartmental metabolic profiles of a conventional mouse strain (C3H/HeJ) (n=5) and its germ‐free (GF) equivalent (n=5). We confirm that the microbiome strongly impacts on the metabolism of bile acids through the enterohepatic cycle and gut metabolism (higher levels of phosphocholine and glycine in GF liver and marked higher levels of bile acids in three gut compartments). Furthermore we demonstrate that (1) well‐defined metabolic differences exist in all examined compartments between the metabotypes of GF and conventional mice: bacterial co‐metabolic products such as hippurate (urine) and 5‐aminovalerate (colon epithelium) were found at reduced concentrations, whereas raffinose was only detected in GF colonic profiles. (2) The microbiome also influences kidney homeostasis with elevated levels of key cell volume regulators (betaine, choline, myo‐inositol and so on) observed in GF kidneys. (3) Gut microbiota modulate metabotype expression at both local (gut) and global (biofluids, kidney, liver) system levels and hence influence the responses to a variety of dietary modulation and drug exposures relevant to personalized health‐care investigations.